VISUAL PERCEPTION IN MIDDLE SCHOOL STUDENTS - Shaima Abed Sharhan (Journals Park Publishing, 2025)
The current study focuses on understanding how middle school students perceive visual information and explores whether there are any differences in this perception based on gender and academic specialization, such as scientific versus literary studies. To accomplish this, the researcher adopted a descriptive approach and utilized the Andre Ray Visual Perception Test. This test was given to a group of 300 randomly selected male and female middle school students. After collecting the data, the researcher analyzed it using appropriate statistical methods to draw meaningful conclusions. The findings reveal that middle school students do indeed have the ability to perceive visual information, as shown by their test responses. Interestingly, the study found no significant differences in visual perception between male and female students, indicating that both genders are equally motivated and knowledgeable as they advance to the preparatory stage. However, differences in visual perception were noted among students based on their academic focus—scientific or literary. These differences are likely due to the distinct teaching and training methods used in each specialization, which significantly influence the students' experiences. Specifically, students in the scientific branch seem to better utilize visual perception to generate and practically apply ideas. The research concludes with several recommendations and suggests potential topics for future studies in this field.
Keywords: Visual Perception, Middle School Students, Gender Differences, Academic Specialization, Teaching Methods.